CHARACTERISTICS AND DISTRIBUTION OF UNMET NEED SOUTH SUMATRA BASED ON GEOSPATIAL - Nina Damayati; Murjainah Murjainah; Maharani Oktavia; Eni Heldayani; Mirna Taufik (Universitas Sebelas Maret (UNS), 2023)
Unmet need in South Sumatra in 2019 was 11.13% and in 2021 the number of unmet need was 15.23%, this figure had increased quite significantly and also still did not fulfill the work agreement of the BKKBN representative for South Sumatra Province which targeted 8.07% That is, this achievement, when referring to BKKBN's target of reducing unmet need for family planning, can be said to have not decreased significantly. The purpose of this study is to determine the characteristics and distribution of Unmet Need in South Sumatra on a geospatial basis. The method in this study uses a quantitative descriptive approach by utilizing secondary data from the 2017 IDHS as well as data on Indonesian families for 2021 conducted by the BKKBN. The treatment of unmet need data is to determine the characteristics and distribution of unmet need data in South Sumatra Province by processing data, analyzing data, and producing geographically referenced outputs. Characteristics of unmet need occur mostly in PUS aged over 35 years with more than two children, the highest education level is at the elementary school level of 11.8% and living in urban areas. The results obtained in the field are that there are many unmet needs due to the impact of the Covid-19 pandemic where many PUS are afraid to access contraceptives at health facilities, complete large-scale social activities, and terminate employment.